ANALISIS TINDAK TUTUR ILOKUSI DALAM DIALOG NASKAH DRAMA PEACE KARYA PUTU WIJAYA DAN RELEVANSINYA DENGAN MATERI AJAR SASTRA DI SEKOLAH MENENGAH ATAS - Rasa, Maria Puspita Destaningtyas Bening; Andayani, Andayani; Ulya, Chafit (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to describe and explain: (1) the form of illocutionary speech acts in Putu Wijaya’s Peace drama script dialogue; (2) the function of illocutionary speech acts in Putu Wijaya’s Peace drama script dialogue; and (3) the relevance of illocutionary speech acts in Putu Wijaya’s Peace drama script dialogue and literature teaching materials in senior high school. This research is a qualitative descriptive research with type of pragmatic approach. Sources of data was a document which is the Putu Wijaya’s Peace drama script dialogue. The technique for taking the subject of this research was done by purposive sampling. Data collection was done by document analysis. Theory triangulation is Searle’s illocutionary speech acts and data sources triangulation in the form of informants was used for validity test of the data. Data analysis in this study was using data analysis according to Miles and Huberman with the flow model. The results of the study are as follows. First, from five form of illocutionary speech acts, the most dominant form is directif form. Second, the most dominant fuction of illocutionary speech acts is directif requestives fuction and directif requirements function. Third, the Putu Wijaya’s Peace drama script dialogue fulllied three important aspects of teaching materials (1) language aspects; (2)psychology aspects; and (3) culture based  aspects; and the curriculum that been used.